Prevalence and management of depressive symptoms in coronary heart disease patients and relationship with cardiovascular prognosis: a prospective cohort study - Yewei Pan; Yequn Chen; Shenglin Wu; Pengxiang Ying; Zishan Zhang; Xuerui Tan; Jinxiu Zhu (BMC Psychiatry, 2024)
Abstract Aims Depressive symptoms are comorbid with coronary heart disease (CHD). There is a controversial debate about whether screening and intervention for depressive symptoms could improve cardiovascular prognosis. This study characterizes the prevalence, characteristics, cardiovascular prognosis and management need of depressive symptoms among CHD patients. Methods CHD patients were recruited between November 18, 2020 and November 26, 2021. Depressive symptoms were evaluated with the Patient Health Questionnaire (PHQ-9). During the 12-month follow-up, cardiovascular disease (CVD) was the endpoint. Time-to-event data were estimated by Kaplan-Meier curves and Cox models. Results Of 582 patients (25% women), 21.0% had mild depressive symptoms, and 7.5% had moderate-to-severe depressive symptoms during hospitalization. Mild and moderate-to-severe depressive symptoms were risk factor-adjusted predictors of the primary composite endpoints (adjusted HR = 2.20; 95%CI 1.19–4.03, and adjusted HR = 2.70; 95%CI 1.23–5.59, respectively). Platelet count and low-density lipoprotein were higher in mild depressive symptoms compared to no depressive symptoms. Conclusion Depressive symptoms are prevalent in CHD patients. Mild and moderate-to-severe depressive symptoms are associated with higher risk of further CVD in CHD patients. Platelet function and behavioral mechanisms may contribute to this association. Trial registration This research was registered at https://www.chictr.org.cn . Full data of first registration is 11/09/2020. The registration number is ChiCTR2000038139.